SISTEM INFORMASI PEMBELAJARAN DIGITAL BERBASIS WEB PADA MATERI PEMBELAJARAN BASIS DATA KELAS XI RPL SMK PEMBANGUNAN AMPEL - Indra Ava Dianta; Ahmad Ashifuddin Aqham; Budi Hartono; Sri Lestari (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Ampel Development Vocational School is a private vocational high school located on JL. Baru Kaligentong Village, Gladagsari District, Boyolali Regency. Ampel Development Vocational School has 3 majors, namely RPL (Software Engineering), AK (Accounting), and TBSM (Motorcycle Engineering and Business). The implementation of the learning activity process at the Development Vocational School is still conventional. The aim of this research is to create a web-based digital learning information system that can support the student learning process at Ampel Development Vocational School. The system development method used is R&D (Research and Development) and uses Unifield Modeling Language (UML) modeling using Use Case Diagrams, Activity Diagrams. The results of this research are able to support the teaching and learning process at Ampel Development Vocational School by using a web-based digital learning information system that can be used by teachers and students by accessing it via the internet.